Group I mGluR Induced LTD of NMDAR-synaptic Transmission at the Schaffer Collateral but not Temperoammonic Input to CA1 - Fitzjohn, Stephen; Bashir, Zafar; Farrow, Paul (Current Neuropharmacology, 2016)
NMDA receptors are composed of multiple subunits and are crucial in the induction of synaptic plasticity and learning and memory. In this study, application of the group I mGlu receptor agonist, DHPG, caused LTD of NMDA-EPSCs (DHPG-LTDNMDA) of the Schaffer collateral, but not of NMDA-EPSCs of the temperoammonic pathway onto CA1 neurons of the hippocampus. DHPGLTDNMDA did not alter the sensitivity of NMDA-EPSC to the GluN2B-antagonist, Ro25-6981, indicating that the postsynaptic NMDA receptor subunit composition remained unchanged following DHPG-LTDNMDA. Furthermore, blockade of GluN2B receptors did not affect the induction of DHPG-LTDNMDA. These results demonstrate a difference in the plasticity of NMDA receptors between two synapses onto the same CA1 neuron, but indicate that the subunit composition of NMDA receptors does not account for this difference.
Keywords: DHPG